2014
DOI: 10.1002/mren.201400003
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic-Alkyd Hybrids: Secondary Nucleation, Particle Morphology, and Limiting Conversions

Abstract: The chemical incorporation of an unsaturated alkyd into an acrylic polymer created via miniemulsion polymerisation was studied. The variation of the number ratio of polymer particles to initial droplets with conversion, and changes in individual monomer conversions with increasing alkyd levels were the main quantities used to study the effect of increasing alkyd quantity in the hybrid system. Homogeneous nucleation was more significant in systems rich in the more hydrophilic methyl methacrylate (MMA). Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…[12] The performance of the composite latex particles is directly affected by their morphology and due to its practical importance, particle morphology has received a considerable attention in the literature. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Several authors reported theoretical approaches aimed at predicting the particle morphology, but most of the methods are based on two limiting assumptions: either the polymer chains do not move from the point that they are formed [25,[27][28][29][30][31] or the equilibrium morphology is attained instantaneously. [11,[32][33][34][35][36][37][38][39][40] There are only few works in the literature that take into account all relevant kinetic and thermodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The performance of the composite latex particles is directly affected by their morphology and due to its practical importance, particle morphology has received a considerable attention in the literature. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Several authors reported theoretical approaches aimed at predicting the particle morphology, but most of the methods are based on two limiting assumptions: either the polymer chains do not move from the point that they are formed [25,[27][28][29][30][31] or the equilibrium morphology is attained instantaneously. [11,[32][33][34][35][36][37][38][39][40] There are only few works in the literature that take into account all relevant kinetic and thermodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of acrylic/alkyd hybrid particles, ,,, as well as the morphologies of films cast from these hybrid particles latexes, ,, has been widely studied. For example, Goikoetxea et al synthesized acrylic/alkyd hybrid particles having a core–shell morphology with a hydrophobic alkyd resin core and an acrylic polymer shell.…”
Section: Introductionmentioning
confidence: 99%
“…Miniemulsion polymerization represents an alternative for synthesizing latexes with the efficient compatibilization of a preformed resin in the polymer particles. Miniemulsion polymerization was previously employed for producing alkyd/acrylic, polyurethane/acrylic, and polybutadiene/polystyrene nanoparticles . Recently, miniemulsion polymerization was successfully employed for synthesizing 20% solid content acrylic/MF latexes with post‐crosslinking capability as an alternative for avoiding face components separation during film formation .…”
Section: Introductionmentioning
confidence: 99%